Corrosion and Low Cycle Fatigue Behaviour of Surface Modified Ti-13Nb-13Zr Alloy - Kumar, Pramod (IIT(BHU) Varanasi, 2022)
Abstract is available in the attachment
This Thesis is submited by Pramod Kumar of IIT(BHU) Varanasi.
Keywords: Corrosion; Fatigue; Surface; Alloy